Tren dan Peluang Riset Integrasi Augmented Reality dan Deep Learning dalam Pembelajaran IPA : Suatu Analisis Bibliometrik - Elvaretta Efendi; Asrizal (Postgraduate, University of Mataram, 2025)
The integration of technology and innovative learning approaches is essential to promote students’ 21st-century skills. Augmented reality and deep learning approaches offer significant potential to support contextual, immersive, and meaningful science education. However, systematic reviews mapping the integration of both within science learning remain limited. This study aims to identify trends, directions, and research opportunities related to the integration of augmented reality and deep learning in science education from 2015 to 2025. A bibliometric analysis was conducted using data retrieved from the Scopus database and analyzed with VOSviewer through visualizations of publication growth, keyword co-occurrence, trend overlays, density maps, and subject area distributions. The results reveal a notable increase in publications in 2024, the emergence of thematic clusters linking technology, pedagogy, and transformational values, as well as a recent shift of augmented reality toward experience-based media. The findings also highlight the opportunities for classroom implementation and the need to strengthen pedagogical designs rooted in deep learning. The multidisciplinary nature of this research opens collaboration across education, technology, environmental science, educational psychology, and media design. These results emphasize the importance of integrating augmented reality and deep learning in designing innovative, globally responsive, and 21st-century skill-oriented science education.